Determinants of Tunisian Consumers’ Willingness to Pay for Organic Cereal Products - Mouna Helali; Emna Ouertani; Mohamed Zied Dhraief (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Investigating Tunisian consumer attitudes about organic cereal products and the factors influencing their willingness to pay a premium price for them are the goals of this paper. Based on a face-to-face exploratory survey of Tunisian household heads, a descriptive analysis and a binomial logistic regression model were used to investigate the factors that would influence Tunisian consumers' willingness to pay more for sustainable organic cereal purchases. According to the study, 20% and 31% of the consumers surveyed indicated that they would be willing to pay an extra 10% or 5% on top of the initial purchase price to buy an organic product, respectively. The outcomes of the binary logistic regression model demonstrate that several factors are influencing. Factors such as consumer sustainability value, desire to pay more for quality, quality/price relationship, health value, and economic value determine customers' willingness to pay a premium price for organic cereal products. These elements must be taken into consideration by producers and processors of organic cereals while making managerial choices.